Language Education, Politics and Technology in South Asia: Shaping Inclusive Societies, Identities, and Futures (Routledge Research in Language Education, 2025)
Bringing together research from the fields of linguistics, education and technology within the dynamic context of South Asia, this timely book investigates the ways in which these fields interact with each other against the backdrop of technological innovation, linguistic diversity and socio-political transformation. Developing and expanding on findings and insights originating from a conference organised by the Education South Asia Initiative at the University of Oxford, this interdisciplinary book features academic reflections on language politics and diversity as well as empirical insights on linguistic, educational and technological transformations in the region. Featuring analytical and methodological approaches to the study of language and education, chapters range in context from India, Bangladesh, Nepal, Pakistan and Sri Lanka, and address a range of issues such as the marginalisation of languages in education and policy, the interactions between language and social hierarchies in the South Asian context, and technology’s impact on language education, acquisition, usage and preservation. Ultimately initiating dialogue on the need for positive changes in language, education research and policy, this book will appeal to scholars, researchers and postgraduate students in the fields of language education, international and comparative education, and education and technology. Policymakers in international development and sociolinguistics may also find the volume of use.